2021
DOI: 10.1097/scs.0000000000007995
|View full text |Cite
|
Sign up to set email alerts
|

End-to-Trunk Masseteric to Facial Nerve Transfer With Selective Neurectomy for Facial Reanimation

Abstract: Objective: To examine functional outcomes following end-totrunk masseteric to facial nerve transfer in patients with chronic flaccid facial paralysis. Design: Retrospective chart review. Setting: Tertiary-care private practice setting. Participants: Patients with complete unilateral facial paralysis of less than 24 months duration. Interventions: Direct end-to-trunk masseteric to facial nerve anastomosis.Outcome measures: Outcome measures included time to first movement, development of synkinesis, and an objec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Finally, as in the primary surgery, the wound is closed after drainage [ 13 ]. For complete unilateral facial paralysis, an effective and safe procedure called end-to-trunk masseteric to facial nerve transfer has been performed, resulting in a natural-looking smile [ 21 ]. Decompressing the facial nerve did not provide any advantages in cases of traumatic facial paralysis resulting from closed-head injuries [ 22 ].…”
Section: Reviewmentioning
confidence: 99%
“…Finally, as in the primary surgery, the wound is closed after drainage [ 13 ]. For complete unilateral facial paralysis, an effective and safe procedure called end-to-trunk masseteric to facial nerve transfer has been performed, resulting in a natural-looking smile [ 21 ]. Decompressing the facial nerve did not provide any advantages in cases of traumatic facial paralysis resulting from closed-head injuries [ 22 ].…”
Section: Reviewmentioning
confidence: 99%
“…As selective neurectomy is often performed with other procedures, simultaneous surgeries (e.g. rhytidectomy, lid surgery and concurrent facial reanimation procedures) may confound direct outcome analysis [17 ▪ ,24,27]. Postoperative care also varies between institutions, leading to differences in chemodenervation and neuromuscular retraining in the perioperative period [16 ▪▪ ].…”
Section: Reviewmentioning
confidence: 99%
“…Vincent et al [24] also showed improvement in synkinesis and smile symmetry using efface. Leader et al [27] also combined masseteric-facial anastomosis with MSN, and reported dynamic movement with a more natural smile postoperatively. SAQ scores have been shown to decline following selective neurolysis [23].…”
Section: Reviewmentioning
confidence: 99%
“…There is minimal donor site morbidity with masseter nerve transfer, and complication rates are generally low [41]. Synkinesis rate is lower than with hypoglossal nerve anastomosis [36,42,43]. In the study by Murphy et al [38], of 183 that underwent masseteric nerve transfer, 12 patients were reported to have complications, including four with masseter atrophy.…”
Section: Masseter Nerve Transfermentioning
confidence: 99%